Harold Stassen : Eisenhower, the Cold War, and the Pursuit of Nuclear Disarmament - Kaplan, Lawrence S. (Book collections on Project MUSE., 2018)
Harold Stassen garnered accolades as the 'boy wonder' governor of Minnesota. When Dwight D. Eisenhower was elected, Stassen was named director of the Mutual Security Administration and then became the president's special assistant for disarmament. In this nuanced biography, Lawrence S. Kaplan demonstrates that Stassen's role in Eisenhower's White House deserves more analysis than it has as yet received.